Endothelial cell modulation of cardiomyocyte gene expression - Jiang, Fan; Rehberg, Franziska; Ullrich, Nina D.; Hecker, Markus; Wagner, Andreas H. (Experimental cell research, 2019)
The anatomic arrangement of microvascular endothelial cells and cardiomyocytes in vivo enables close interactions among these cells. In our in vitro co-culture system, ANP and BNP expression in the mouse atrial cardiomyocyte cell line HL-1 and subsequent ANP release were significantly upregulated when co-cultured with mouse cardiac microvascular endothelial cells or exposed to endothelial cell-conditioned medium. Endothelin-1 (ET-1) activation of endothelial cells remarkably enhanced their paracrine effect on cardiomyocyte gene expression, suggesting that ET-1 stimulation of endothelial cells affects expression of fetal genes such as ANP and BNP in adult cardiomyocytes through paracrine signalling. Exposure of HL-1cells and murine induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) to authentic angiopoietin-2 (Ang2) caused a concentration-dependent decrease in ANP expression while ET-1-induced ANP expression was augmented by low but inhibited by high concentrations of Ang2. FK506-mediated inhibition of the calcineurin-NFAT pathway in the HL-1cells selectively inhibited the stimulatory effect of the conditioned medium derived from ET-1-pre-stimulated endothelial cells on cardiomyocyte fetal gene expression. Combined with previous results indicating a crucial role for ANP and BNP in cardiac homeostasis, our findings provide further evidence that paracrine signalling by cardiac microvascular endothelial cells modulates cardiomyocyte function.
Gesehen am 24.10.2019